2(5-h)-5(3-2h)=5h+10

Simple and best practice solution for 2(5-h)-5(3-2h)=5h+10 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2(5-h)-5(3-2h)=5h+10 equation:



2(5-h)-5(3-2h)=5h+10
We move all terms to the left:
2(5-h)-5(3-2h)-(5h+10)=0
We add all the numbers together, and all the variables
2(-1h+5)-5(-2h+3)-(5h+10)=0
We multiply parentheses
-2h+10h-(5h+10)+10-15=0
We get rid of parentheses
-2h+10h-5h-10+10-15=0
We add all the numbers together, and all the variables
3h-15=0
We move all terms containing h to the left, all other terms to the right
3h=15
h=15/3
h=5

See similar equations:

| 2(x+4)+1=-1 | | -4r+8=5r-10 | | 30+4y-4=13y-10-3y | | 39=-8(1+x)-(-1-4x) | | 4-z=7 | | 4.1=8.6+0.9x | | 8x+9=7-(2x-3) | | 41=8.6+0.9x | | 4(0.5f-0.2)=6+f | | 1250000000/x=3 | | 8x+4=3(x-3)+7 | | 5(4x+2)=36 | | 144=4x+4(3×+4 | | 2x+5x=37 | | 8x-5x+1/18=1/6 | | 3.5x-4.9=22.75 | | 79=7x-4(-2x+14 | | 2.5+10m=8.32 | | 4(5x-3)+5x+5=11 | | 6q^2-q=1 | | -x+4/5=x+1/2+2/5 | | 2(x+2)+x=-11 | | 39x+36-12x2=0 | | 2/3z+2=3(5/6z+1) | | -5(5)=x | | 6x+1/2=5/6 | | y/6-3=6 | | 2/3x-3=2+5/6x | | 5(x-1)+4=-1 | | 2/3x-2=6+4/9x | | 3(x-3)-x=-5 | | 5(x+4)-7=6x+8 |

Equations solver categories